Determination of Trace Selenium in Urine and Water Samples by Hydride Generation Atomic Absorption Spectrometry After Preconcentration/Separation with Modified Organobentonite with Dithizone - Zhang, Dong; Sheng Zhao, Guang (Asian Journal of Chemistry, 2013)
This paper describes a novel application of modified organobentonite with dithizone (D-O-bentonite) to the preconcentration and separation of selenium using a hydride generation-atomic absorption spectrometry (HG-AAS). A new method for the determination of trace selenium in urine and water has been introduced using a solid-phase extraction agent of D-O-bentonite. Optimal experimental conditions for the adsorption and elution of the selenium, including amount of acid, contact time, eluent volume and co-existing ions have been investigated. The result showed that the selenium could be adsorbed on the D-O-bentonite because of the complexation of dithizone with Se(IV). The adsorbed quantity was affected by the type and amount of acid and contact time. In 50 mL solution, when the dosage of HCl was 20-30 mL and the shaking time was 10 min, the adsorption capacity was 12.09 mg/g. The selenium adsorbed on the D-O-bentonite could be completely eluated by using 5 mLof 1 g/L sodium hydroxide solution. With a preconcentration factor of 100, the detection limit of this method for selenium was 0.0076 μg/L. The proposed solid-phase extraction methodology has been successfully applied to the pre-concentration/separation of selenium in the human urine and water samples with satisfied results.